Who’s the scariest of them all? Depictions of evil women in Greek folktales - Papailia, Artemis (International Journal of Language and Literary Studies, 2024)
This study aims to investigate the portrayal of demonic women in Greek folktales and their significance in reflecting societal perceptions of femininity. We selected 17 editions of folktales in the Greek publishing industry as our primary source material and utilized content analysis as our method of analysis. Negative values such as ferocity, malice, brutality, wickedness, and ugliness were used as criteria to study the demonic woman's external appearance and personality. Vladimir Propp’s Morphologie du conte (1970) served as a reference for examining the demonic woman's qualities such as name, origin, social position, age, external characteristics, and peculiarity of her appearance. We also focused on the demonic woman's actions and relationship with the hero/heroine to highlight the terrifying aspects of her inner world. The study sheds light on how the representation of demonic femininity in Greek folktales reveals societal and traditional assumptions about female gender. Our findings aim to demonstrate the different faces of the diabolical women in Greek folktales and present a collective representation of the demonic.